Analysis of Muscle Lipidome in Juvenile Rainbow Trout Fed Rapeseed Oil and Cochayuyo Meal - John Quiñones; Rommy Díaz; Jorge F. Beltrán; Lidiana Velazquez; David Cancino; Erwin Muñoz; Patricio Dantagnan; Adrián Hernández; Néstor Sepúlveda; Jorge G. Farías (Biomolecules, 2022)
This study aimed to analyze the effects on the lipidome of juvenile Oncorhynchus mykiss muscle fed 90% Brassica napus “rapeseed” oil and different amounts of Durvillaea antarctica “Cochayuyo” meal (1.5, 3 and 6%) as a replacement for cellulose. The analysis allowed for the identification of 329 lipids, mainly represented by phospholipids and fatty esters. The inclusion of Brassica napus oil significantly increased the levels of C18:2 species and fatty esters of hydroxylated fatty acids, which could play a bioactive role in human health. One of the most abundant lipids in all fillets was Phosphatidylcholine 33:6, which, according to the literature, could be considered a biomarker for the identification of Oncorhynchus mykiss. In all experimental diets, the species Phosphatidylethanolamine 15:1-18:24 showed four-fold higher levels than the control; increments of n-3- and n-6-rich phospholipids were also observed. Diets containing Durvillaea antarctica meal did not generate more significant variation in fish muscle phospholipids relative to the muscle of the rapeseed-oil-only group. These lipid species consist of medium- and long-chain fatty acids with different degrees of unsaturation. Still, it appears that the rapeseed oil masks the lipid contribution of the meal, possibly due to the low levels of total lipids in the macroalgae.